'Antlers inside': are the skull structures of beaked whales (Cetacea: Ziphiidae) used for echoic imaging and visual display?. (25th July 2014) - Gol'din, Pavel
<x xml:space="preserve">Abstract</x> Skulls of many living and extinct beaked whales (Ziphiidae) contain various bizarre bone and tooth structures. Many of them show sexual dimorphism in their skull anatomy: males have bizarre skull structures, whereas females do not. Opinions differ as to what the function of these structures might be. Some believe that these are weapons; others, that they are sound transmitters. This article argues that these structures are the means of visual display. Many of the bizarre bone structures of beaked whales are not exposed like 'visuals' of terrestrial tetrapods, but are located deep in soft tissues. Nevertheless, toothed whales recognize objects (including three‐dimensional bodies), using echolocation. So, along with visual means, they can 'see' and 'show' their internal bone structures with echoic imaging and use them as informational sources in social interactions and in individual or species recognition. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 113, 510–515.